Pathways to net zero emissions for the Indian power sector. (January 2023) - Das, Anjana; Saini, Vinay; Parikh, Kirit; Parikh, Jyoti; Ghosh, Probal; Tot, Mario
Abstract: At COP26, India has committed to achieve net zero emissions by 2070. For economy wide net zero, the power system should be first to attain it. This paper explores the role of different technologies, CO2 capture and storage (CCS), nuclear, solar PV and thermal, battery storage, pumped storage, hydro etc. along with energy efficiency in doing so by different target years, 2050 and 2060 and their economic implications. With more intermittent renewables, the issue of balancing hourly demand-supply of both energy and power becomes critical for ensuring the feasibility of a pathway. Hourly availability of different renewable technologies is considered along with hourly variations in electricity demand. Three scenarios are analysed, Business-as-Usual (BAU) scenario assumes current policies to continue, and two Net Zero (NZ) scenarios to achieve net zero emissions by 2050 and 2060. Solar PV, wind onshore and offshore, battery storage are the dominant technologies in achieving net zero emissions. Solar and wind together contribute 85% and 90% of the total generation capacity in 2050 and 2060, respectively. Dispatchable technologies like Coal plant with CCS and nuclear are also important. Results specify Battery with storage hour specifications (1 h, 2 h etc.), so one can plan storage in details. Decarbonisation has significant additional cost and investment requirement over the Business-As-Usual scenario. Respective additional cumulative investment requirements (2030–60) are about 1.6 trillion USD and 1.4 trillion USD in two NZ scenarios. The required policies and measures are also discussed. Highlights: Developing net zero emissions scenarios for the Indian power system. MESSAGE modelling of the power system, balancing energy and load for 288 time slices. Solar PV, wind, battery storage are key technologies to achieve net zero emissions. Net zero emissions impose large increase in investments and electricity supply costs.